Follicular B Cells Promote Atherosclerosis via T Cell–Mediated Differentiation Into Plasma Cells and Secreting Pathogenic Immunoglobulin G. Issue 5 (May 2018) - Tay, Christopher; Liu, Yu-Han; Kanellakis, Peter; Kallies, Axel; Li, Yi; Cao, Anh; Hosseini, Hamid; Tipping, Peter; Toh, Ban-Hock; Bobik, Alex; Kyaw, Tin
Abstract : Objective—: B cells promote or protect development of atherosclerosis. In this study, we examined the role of MHCII (major histocompatibility II), CD40 (cluster of differentiation 40), and Blimp-1 (B-lymphocyte–induced maturation protein) expression by follicular B (FO B) cells in development of atherosclerosis together with the effects of IgG purified from atherosclerotic mice. Approach and Results—: Using mixed chimeric Ldlr −/− mice whose B cells are deficient in MHCII or CD40, we demonstrate that these molecules are critical for the proatherogenic actions of FO B cells. During development of atherosclerosis, these deficiencies affected T–B cell interactions, germinal center B cells, plasma cells, and IgG. As FO B cells differentiating into plasma cells require Blimp-1, we also assessed its role in the development of atherosclerosis. Blimp-1-deficient B cells greatly attenuated atherosclerosis and immunoglobulin—including IgG production, preventing IgG accumulation in atherosclerotic lesions; Blimp-1 deletion also attenuated lesion proinflammatory cytokines, apoptotic cell numbers, and necrotic core. To determine the importance of IgG for atherosclerosis, we purified IgG from atherosclerotic mice. Their transfer but not IgG from nonatherosclerotic mice into Ldlr −/− mice whose B cells are Blimp-1-deficient increased atherosclerosis; transfer was associated with IgG accumulating in atherosclerotic lesions, increased lesion inflammatory cytokines, apoptotic cell numbers, and necrotic core size. Conclusions—: The mechanism by which FO B cells promote atherosclerosis is highly dependent on their expression of MHCII, CD40, and Blimp-1. FO B cell differentiation into IgG-producing plasma cells also is critical for their proatherogenic actions. Targeting B–T cell interactions and pathogenic IgG may provide novel therapeutic strategies to prevent atherosclerosis and its adverse cardiovascular complications. Abstract : Supplemental Digital Content is available in the text.